Impacts of Tele-Centers towards the Development of Communities: A Case Study of Kayonza Telecentres in Rwanda - Richard, Makombe (Kabale University, 2019)
A Research Report Submitted in Partial Fulfillment of Requirements for the Award of Diploma in Library and Information Science of Kabale University